2001
DOI: 10.1053/ajcd.2001.20110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patch test results with a standard series among white and black racial groups

Abstract: The differences in sensitization rates, especially for p-phenylenediamine, may reflect variations in allergen exposure among racial groups or interindividual variations in the N-acetylation (N-acetyltransferase 1 [NAT1] and 2 [NAT2]) capacities of human skin for p-phenylenediamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Few reactions were found to colophony and balsam of Peru. These figures are in line with a previous study from Denmark (1,25), however, lower than reported in out-patient clinic studies (18,28). Moreover, there does not seem to be a concomitant positive patch test to balsam of Peru in fragrance-sensitive patients, which suggests that balsam of Peru is not a reliable marker of fragrance allergy (27).…”
Section: Discussionsupporting
confidence: 89%
“…Few reactions were found to colophony and balsam of Peru. These figures are in line with a previous study from Denmark (1,25), however, lower than reported in out-patient clinic studies (18,28). Moreover, there does not seem to be a concomitant positive patch test to balsam of Peru in fragrance-sensitive patients, which suggests that balsam of Peru is not a reliable marker of fragrance allergy (27).…”
Section: Discussionsupporting
confidence: 89%
“…No association was found between positive patch test results and acetylator status although it was reported that variations in N-acetylation in human skin could account for variations in positivity in patch testing. 10 In a parallel study of the acetylator status among children with atopic dermatitis, an association was found between the severity and site of the atopic dermatitis and acetylator status. 11 However, in this study no such association was found.…”
Section: Discussionmentioning
confidence: 98%
“…Statistical analyses were done using SPSS version. 10 Differences between groups were assessed by the chi-square test. An estimate was considered statistically significant if the P value was <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Allergic or photoallergic contact dermatitis is found in roughly 70% of those with CAD with sunscreen components usually implicated . Para‐phenylenediamine, a known dye allergen, is suggested as a potential sensitizer seen more frequently in patients with SOC . This is believed to be due to exposure to products, such as hair care products, with higher levels of para‐phenylenediamine, which could lead to increased sensitization rates …”
Section: Immune‐mediated Photodermatosesmentioning
confidence: 99%